(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Socialist realism is a form of idealised realism that originated in the Soviet Union and spread to other socialist nations after World War II. It was the official style in the USSR from 1932 to 1988. The representation of communist principles, such as the emancipation of the proletariat, characterises socialist realism. Figures in this style are generally idealised, especially in sculpture, where it often relies on classical sculpting standards. Social realism is a genre of art that realistically shows socially relevant issues, but it should not be confused with other forms of realism in the visual arts. Socialist realism depicted an idealised Soviet Union in a very clear and evident way. Socialist realism was frequently devoid of any kind of nuance or nuanced aesthetic meaning. In this paper a review of Modernism, Postmodernism, Realism, Socialist Realism and Social Realism.